Biomechanical Analysis of Foot–Ankle Complex during Jogging with Rearfoot Strike versus Forefoot Strike - Yaoyong Zhang; Dan Zhang (Applied Bionics and Biomechanics)
Background and Aim. In order to reduce foot and ankle injuries induced by jogging, two-foot strike patterns, rearfoot strike (RFS), and forefoot strike (FFS), were adopted and compared. First, RFS jogging and FFS jogging were experimentally studied, so as to acquire kinematic and kinetic data, including foot strike angle, knee flexion angle, and ground reaction force (GRF). Then, a 3D finite element model of foot–ankle complex was reconstructed from the scanned 2D-stacked images. Biomechanical characteristics, including plantar pressure, stress of metatarsals, midfoot bone, calcaneus and cartilage, and tensile force of plantar fascia and ligaments, were obtained. The results showed that RFS jogging and FFS jogging had a similar change trend and a close peak value of GRF. Since possessing more momentum in the push stage and less momentum in the brake stage, FFS jogging could be in favor of a higher jogging speed. However, FFS jogging produced larger metatarsal stress in the 5th metatarsal and much larger tensile force of plantar fascia, which might cause metatarsal fracture and heel pain. While RFS jogging produced larger plantar pressure in the hindfoot area, larger calcaneus stress, and much larger tarsal navicular stress, which might cause heel tissue injury, calcaneus damage, and stress fracture of naviculocuneiform joint. In addition, talocrural and talocalcaneal joint cartilage could bear jogging loads, as the peak contact pressure were both small in RFS jogging and FFS jogging. Therefore, jogging with rearfoot or FFS pattern should be chosen according to the health condition of foot–ankle parts.